ANALISIS PENGARUH KONFLIK PERAN GANDA, DISIPLIN KERJA, DAN LINGKUNGANpKERJA TERHADAPnKINERJA KARYAWANp PT. GLOBALINDOpINTIMATES DI KLATEN - Sulisvi Sulisvi; Eny Kustiyah; Rochmi Widayanti (JURNAL ILMIAH EDUNOMIKA, 2019)
The research to find out and describe the influence of either simultaneously of partial work-family conflict, work discipline and work environtment. The population was all employees PT. Globalindo Intimates Klaten totaled 1300. The number of samples was determined with the formula Arikunto and the result 100 respondents. Sampling. The questionnaire used for data retrieval. Data analysis technique used was statistic analysis. This F test results work-family conflict, work discipline and work environtment simultaneously effect on employees performance PT. Globalindo Intimates Klaten. The t-test results showed that work-family conflict influential significance effect against the employees performance PT. Globalindo Intimates Klaten. . The t-test results showed that work discipline influential significance effect against the employees performance PT. Globalindo Intimates Klaten. The t-test results show that work environtment does not affect employee performance. Model ultiple regression linier in this research is Y = 4,710 + 0,256XK+ 0,409XD– 0,076XL + e. Determination of the coefficient indicates work-family conflict, work discipline and work environment have influence of 43,3% employees performance PT. Globalindo Intimates. Keywords: Work-Family Conflict, Discipline, Work Environtment, Employees Performance